Gender Equality and Forms of Gender Inequality - Ramdin Ramdin; Muhammad Sanatul Anwar (Journal of Loomingulisus ja Innovatsioon, 2024)
Gender equality and forms of gender inequality that still occur in various parts of the world. Gender equality refers to the equal rights, opportunities, and treatment of women and men in all aspects of life, regardless of gender. The goal is to create a just and equitable society where everyone can reach their full potential. However, reality shows that gender inequality remains a serious problem. Forms of gender inequality include discrimination in access to education, gaps in the workplace, gender-based violence, gender stereotypes, and double burdens for women. Discrimination in education can limit women’s access to quality education, while gaps in the workplace result in differences in pay and promotion opportunities for women. Gender-based violence, such as domestic violence and sexual harassment, is a serious violation of women’s human rights. Gender stereotypes that reduce women’s roles and abilities can also limit their opportunities. The double burden borne by women, namely working outside the home and taking care of household chores, can lead to fatigue and a lack of time for self-development. To achieve gender equality, a collective effort is needed from various parties, such as the government, society, and individuals. These efforts include the elimination of discrimination, law enforcement, education about gender equality, and cultural changes that support equality. By understanding and addressing forms of gender inequality, we can build a just and equitable society for women and men.